TOLVAPTAN USE IN SEVERE NEONATAL AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE (ADPKD): THE PHARMACEUTICAL CHALLENGE. Issue 9 (17th August 2016) - Olalekan, Kazeem; Fox, Andy; Gilbert, Rodney
Abstract : Background: Unlicensed medications are used all the time in the management of diseases in childhood. Tolvaptan (Jinarc®) is a vasopressin V2-receptor antagonist licensed for use to slow the progression of cyst development and renal insufficiency of ADPKD in adults with CKD stage 1 to 3 with evidence of rapidly progressing disease. Studies of animal models implicate the antidiuretic hormone arginine vasopressin and its messenger cyclic adenosine monophosphate (cAMP) as promoters of kidney-cyst cell proliferation and luminal fluid secretion. The suppression of vasopressin release by means of high water intake, genetic elimination of vasopressin, and vasopressin V2-receptor blockade all reduce the cyst burden and protect kidney function1 A Phase 3 trial showed that Tolvaptan, as compared with placebo, slowed down the increase in total kidney volume and decline in kidney function in adults (average 39 yrs) with ADPKD over a 3-year period.2 ADPKD is the most common form of polycystic kidney disease (PKD) typically late in onset and results from mutation of either of two genes: PKD1 and PKD2. Autosomal recessive polycystic kidney (ARPKD), the other form of PKD, is 20 times less common, presents primarily in infancy and childhood, is typically more severe, and commonly associated with hypertension. ARPKD results from mutation of PKHD1. In spite of these differences, there is growing evidence to suggest that ADPKD and ARPKD are more related than previously suspected.3 Bilineal inheritance of PKD1 abnormalities has been reported to cause extremely severe disease resembling ARPKD.4 The use of Tolvaptan in the management of PKD in children is therefore expected to become more important. Aim: To describe the first known UK use of Tolvaptan in a neonate with severe ADPKD and the role of the hospital pharmacist in facilitating the use. Method: The role descriptor of hospital pharmacists produced by the World Health Organisation (WHO) was adapted and used to map the pharmaceutical challenges of using Tolvaptan in this child. The descriptor include: (i) Promotion of rational prescribing of drugs, (ii) Use of specialist pharmacists networks to gain greater expertise; (iii) Monitor compliance and therapeutic response and report adverse drug reactions; (iv) ensure supply of high quality products; (v) partake in planning and implementation of clinical trials. Results: The use of Tolvaptan for indication other than hyponatraemia and other endocrine uses are not routinely commissioned by NHS England. In view of the exceptionality of this case – a severe neonatal form of ADPKD with estimated prevalence of the order of 1 in tens of millions, an Individual Funding Request (IFR) application was made and was approved. The application was supported by financial information provided by the hospital pharmacist who facilitated the application process. Using available information and formulation knowledge, a suspension was eventually recommended and was well tolerated. This resulted in approximately 85% reduction in the cost of treatment over six months. Tolvaptan produced the expected aquaresis and blood pressure reduction. Initial dose of 0.1 mg/kg/day was used and increased according to weight and clinical response. Initial monitoring parameters, which included 4 hourly blood pressure, urine and electrolytes and hepatic function, were recommended. Electrolyte supplements were adjusted accordingly. At 2-month review point, there was no oedema of leg and face but the kidneys were still enlarged. The long term effect on cyst burden and kidney function is being evaluated and will feed into the IFR process. Conclusion: The use of unlicensed medications in children poses a number of pharmaceutical challenges and can be managed through a multidisciplinary approach to treatment intervention. It also re-enforce the paediatric formulation challenge to pharmaceutical companies in which formulation needs are prioritised and existing data are better used to facilitate paediatric formulation development.